Hybrid horizons: navigating career development among Singapore's young professionals in the hybrid work era - Chiow, Alicia (Nanyang Technological University, 2024)
The transition to hybrid work post-pandemic was adopted by many countries, including Singapore. The flexibility offered by hybrid work brought about work-life balance, increased work productivity and a strong focus on professional networking. While these themes surrounding hybrid work remain prevalent in the realm of hybrid work, little research has focused on their effects on career development. Singapore faces an ageing population, and the young will shape the future of work. Hence, this study explores the impacts of hybrid work on young professionals’ career development, investigating if certain identified trends can help to assist in government initiatives like SkillsFuture to better support the young talents’ evolving needs in the workforce. A qualitative study was conducted with 16 participants who shed light on this phenomenon. Work-life balance a priority in work, coupled with the need for support groups and networking opportunities to maintain relevance in the workforce suggests that more can be done to better support the young professionals in navigating the evolving workplace challenges.